2015
DOI: 10.1016/j.aim.2014.11.004
|View full text |Cite|
|
Sign up to set email alerts
|

Odd order Brauer–Manin obstruction on diagonal quartic surfaces

Abstract: We determine the odd order torsion subgroup of the Brauer group of diagonal quartic surfaces over the field of rational numbers. We show that a non-constant Brauer element of odd order always obstructs weak approximation but never the Hasse principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 14 publications
5
42
0
Order By: Relevance
“…where Γ acts trivially on Z n . Now (i) follows from the exact sequence (8). Part (ii) follows from Proposition 4.1, so it remains to establish part (iii).…”
Section: Kummer Varieties Attached To Products Of Abelian Varietiesmentioning
confidence: 94%
“…where Γ acts trivially on Z n . Now (i) follows from the exact sequence (8). Part (ii) follows from Proposition 4.1, so it remains to establish part (iii).…”
Section: Kummer Varieties Attached To Products Of Abelian Varietiesmentioning
confidence: 94%
“…Another example of a rationally connected variety X over a number field k such that X(A k ) Br(X) = X(A k ) Br 1 (X) is given in [DLAN17]. Transcendental elements and their influence on the Brauer-Manin set have received a lot of attention for other classes of varieties as well (see [Wit04], [Ier10], [HVAV11], [Pre13], [HVA13], [IS15], [New16], [CV15], [MSTVA16] for examples of K3 and Enriques surfaces for which transcendental elements play a role in the Brauer-Manin set).…”
Section: Over Number Fields: General Contextmentioning
confidence: 99%
“…The analogous problem for X(A Q ) Br 1 (X) was solved by Bright [Bri06]. It is known that transcendental elements cannot be ignored in this context: there exist diagonal quartic surfaces X over Q such that X(A Q ) Br(X) = X(A Q ) Br 1 (X) (see [Ier10], [Pre13], [IS15]). There also exist K3 surfaces X over Q such that…”
Section: K3 Surfacesmentioning
confidence: 99%
“…It should be noted that Ieronymou and Skorobogatov [23] have shown that odd-order elements in the Brauer groups of diagonal quartic surfaces over Q, when they do exist, can never obstruct the Hasse principle. They do this by calculating that, if A has order p = 3 or 5 in Br X/ Br Q, then the corresponding evaluation map A : X(Q p ) → Br Q p [p] is surjective.…”
Section: Vanishing Of Brauer-manin Obstructionsmentioning
confidence: 99%